Modified tubeless minimally invasive percutaneous nephrolithotomy for management of renal stones in children: A single-centre experience. Issue 4 (2nd October 2019) - Sebaey, Ahmed; Abdelaal, Ashraf; Elshaer, Alaa; Alazaby, Hisham; Kadeel, Wael; Soliman, Tarek; Elbarky, Ehab
ABSTRACT: Objectives : To evaluate the safety, effectiveness and morbidity, as well as the usefulness of a modified supine mini-percutaneous nephrolithotomy (PCNL) for managing renal stones in children. Patients and methods : We studied 50 children, from September 2017 to September 2018, who were aged 4–16 years with a single renal pelvic or calyceal stone of <2 cm. We used a 9-F short ureteroscope through a 16-F metal access sheath with an alternative approach that allows a second percutaneous procedure using the same tract. If a residual stone was present, we recovered the track back through the exteriorised ureteric catheter at the flank. Results : Of all 50 patients, 48 (96%) underwent the modified supine mini-PCNL technique, which produced a primary stone-free rate of 80% that increased to 100% after treating the residual stones by a second look. The mean operative and fluoroscopic times were 89.10 and 7.68 min, respectively. One case (2%) had significant bleeding and one case (2%) had pelvic perforation; and a nephrostomy tube was inserted in both cases. The mean haemoglobin drop was 0.91 g/dL ( P < 0.001). The mean hospital stay was 1.42 days and the mean pain score was 2.08, the pain score was 5 in the two cases in which a nephrostomy tube was inserted. Conclusion : The modified supine mini-PCNL is a safe and effective method for managing renal stones in children, with less postoperative pain and discomfort, less analgesic requirement, and provides access back for a second look. Abbreviations: ESWL: extracorporeal shockwave lithotripsy; Hb: haemoglobin: PCNL: percutaneous nephrolithotomy; SFR: stone-free rate